Highly fractionated S-type granites from the giant Dahutang tungsten deposit in Jiangnan Orogen, Southeast China: geochronology, petrogenesis and their relationship with W-mineralization - Huang, Lan-Chun; Jiang, Shao-Yong (Lithos, 2014)
The Dahutang deposit is a newly discovered tungsten deposit, which is within the largest ones in the world with an estimated WO3 reserve of 2 million tones. W-mineralization is considered to be related with the Late Mesozoic granites in the district. However, the precise emplacement ages, sources of these granites, and their relationship with mineralization are not well understood. In this study, four mineralization-related granite bodies (G1 to G4) were identified in the Dahutang mining area, including the porphyritic-like two-mica granite (G1) (the size of its phenocrysts is from 0.2×0.2cm2 to 0.7×0.3cm2), middle- to fine-grained muscovite granite (G2), porphyritic two-mica granite (G3) (the size of its phenocrysts is from 0.3×0.2cm2 to 0.9×0.6cm2), and fine-grained two-mica granite (G4). LA-ICP-MS U–Pb dating of zircon grains from these four granite bodies yields emplacement ages of 144.0±0.6Ma, 133.7±0.5Ma, 130.3±1.1Ma and 130.7±1.1Ma, respectively. Granites contain quartz, K-feldspar and plagioclase as the principal phases, accompanied by muscovite, minor biotite and accessory minerals. Geochemically, the granites are strongly peraluminous, have high contents of alkalis, high Ga/Al ratios, enrichment in LILEs (such as Rb) and depletion in HFSEs (such as Zr, Nb, Ti). The granites formed at relatively low temperatures (679°C to 760°C) according to zircon saturation temperatures. Geochemical fractionation trends recorded by whole rocks and minerals permit to distinguish and model the two fractional crystallization series G1 and G2–G4. Fractional crystallization of orthoclase and albite in G1 and G4, and orthoclase and oligoclase in G2 and G3 was the principal process of magmatic differentiation that controlled Rb, Sr and Ba concentrations, whereas rare earth elements were fractionated by accessory minerals, such as apatite, zircon and monazite. The geochemical data suggest that the rocks are highly fractionated S-type granites. The granites show bulk rock εNd(t) values in the range of −9.37 to −5.92 and zircon εHf(t) values from −8.44 to −2.13, with late Mesoproterozoic TDMC ages for both Nd and Hf isotopes. Geochemical and isotopic data suggest that these highly fractionated S-type granites G1 and G2–G4 were originated from two episodes of partial melting of different protoliths which have analogous components of metamorphosed pelitic rocks from the Neoproterozoic Shuangqiaoshan Group, which are enriched in tungsten. Extreme fractional crystallization resulted in further enrichment of tungsten in the evolved granitic magma. The new presented data together with previously published data suggest that the Dahutang granitic complex was likely to be formed during lithospheric thinning and asthenospheric upwelling process in Eastern China. •Dahutang deposit is a new discovered largest tungsten deposit in the world.•The granites at Duhutang are highly fractionated S-type granites.•The granites were originated from two episodes of partial melting of different protoliths.•The G1 granite intruded during the first stage of 144Ma.•The G2–G4 granites intruded during the second stage of 130–134Ma.